R/V NATSUSHIMA NT07-13 Cruise Data - JAMSTEC (JAMSTEC, 2007)
[CRUISE DATA] This site includes a cruise dataset acquired in NT07-13 on R/V NATSUSHIMA from 2007-07-03 to 2007-07-09.
Observation contents: Expendable Bathythermograph
Keywords: Research cruise; R/V NATSUSHIMA; oceans